Pengaruh Likuiditas, Profitabilitas Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Moderating - Sitompul, Clarisa Florentina; Minan, H. Kersna; Arief, Muhammad (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study was conducted with the aim of determining the effect of liquidity, profitability, and company size on company value with capital structure as a moderating variable. This type of research is quantitative research with a causality approach. The population used in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021 and there were 28 companies taken so that the total sample was 140. The sampling technique used the purposive sampling method. The analysis method of this study uses multiple linear regression and Moderated Regression Analysis. The results of the study indicate that profitability has a significant effect on firm value, while liquidity and firm size do not have a significant effect on firm value. Capital structure can moderate the relationship between profitability and firm size on firm value. Capital structure does not moderate the relationship between liquidity and firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021.